Regime Type, Inequality, and Redistributive Transfers in Developing Countries - Marina Dodlova; Anna Giolbas (German Institute of Global and Area Studies (GIGA), 2015)
The debate on whether democracy and inequality increase the level of redistribution in a country is still ongoing. We construct a model that predicts a higher probability of redistribution in democracies than in autocracies. Further, with higher initial inequality, there should be more redistribution in democracies but not necessarily in autocracies. We test these predictions using data on social transfers in developing countries for the period 1960-2010. We confirm that democracy increases redistribution and, to some extent, that there is more redistribution with rising inequality. Hence, on the basis of a direct measure of redistribution, we present evidence to confirm the median voter theorem.
Keywords: D72; H53; H75; 330; regime type; inequality; redistribution; median voter theorem